Carbapenemase and ESBL genes with class 1 integron among fermenting and nonfermenting bacteria isolated from water sources from India. (1st July 2020) - Singh, F.; Hirpurkar, S.D.; Rawat, N.; Shakya, S.; Kumar, R.; Kumar, S.; Meena, R.K.; Rajput, P.K.; Kumar, J.
Abstract: The present study was aimed to detect the carbapenemase, extended‐spectrum β ‐lactamase (ESBL), and intI1 gene of class 1 integron among fermenting ( n = 61) and nonfermenting ( n = 10) bacterial isolates recovered from water samples ( n = 128). Isolates were identified by 16S rRNA sequencing. These isolates showed reduced‐susceptibility to third‐generation cephalosporins and carbapenems. The isolates varied in number and size of plasmids (2 kb to >20 kb). Plasmid DNA screening showed 5·6, 7, 11·2 and 26·7% prevalence of bla KPC, bla NDM, bla SHV and bla TEM genes respectively. Diverse bla NDM ( bla NDM‐1 and bla NDM‐4 ) and bla SHV subtypes ( bla SHV‐2 and bla SHV‐11 ) were recorded, unlike the single allelic bla KPC ( bla KPC‐2 ) and bla TEM ( bla TEM‐1 ) gene. Of the total 27 bla ‐gene‐producing bacterial isolates, seven isolates co‐harboured the carbapenemase genes ( bla NDM or bla KPC or the both) along with the ESBL genes ( bla SHV or bla TEM ). The intI1 gene of class 1 integron was detected among 12 (44·4%) of ESBL‐ and/or carbapenemase‐harbouring isolates. Gene transferability was seen among four of the 10 Enterobacteriaceae donors. Carbapenemases and ESBLs with class 1 integron among aquatic environmental isolates raise the serious issue of the biosecurity and health of the ecosystem. Significance and Impact of the Study: Anthropologically affected and polluted environment harbours the resistance threats, where a diverse bacterial species maintain, develop and exchange genetic determinants that constitute a risk to human and ecological health. The antimicrobial resistance (AMR) in Enterobacteriaceae and non‐ Enterobacteriaceae bacteria caused the failure of the therapy of last resort (carbapenems) and thus lead to life‐threatening infections affecting public health. Surveillance and monitoring of AMR could be important for epidemiological, diagnostic testing and control of pathogens. This is a point‐prevalence study reporting the comparative occurrence and co‐occurrence of carbapenemase and extended‐spectrum β ‐lactamase genes among fermenting and nonfermenting bacteria isolated from the aquatic environment in India.